The influence of magnetite-based additives on the physicomechanical and special properties of sand-resin mixtures - S. V. Koreniugin; S. L. Rovin; P. P. Kuzenkov; M. A. Rypinski (Литьë и металлургия)
The article presents the results of studies of the effect of FerroSAND® magnetite-containing additive on the basic physicomechanical and special properties of cold-hardening sand-resin mixtures used in alpha-set and furan processes. Based on the research results, recommendations are given for the rational use of Ferrosan® additives in mixtures with furan, carbamide-furan and phenol-formaldehyde binders.